Novel Approaches to Improve the Efficacy of Immuno-Radiotherapy - Shevtsov, Maxim; Sato, Hiro; Multhoff, Gabriele; Shibata, Atsushi (Frontiers in Oncology, 2019)
Radiotherapy (RT) has been applied for decades as a treatment modality in the management of various types of cancer. Ionizing radiation induces tumor cell death, which in turn can either elicit protective anti-tumor immune responses or immunosuppression in the tumor micromilieu that contributes to local tumor recurrence. Immunosuppression is frequently accompanied by the attraction of immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs), M2 tumor-associated macrophages (TAMs), T regulatory cells (Tregs), N2 neutrophils, and by the release of immunosuppressive cytokines (TGF-b, IL-10) and chemokines. Immune checkpoint pathways, particularly of the PD-1/PD-L1 axis, have been determined as key regulators of cancer immune escape. While IFN-dependent upregulation of PD-L1 has been extensively investigated, up-to-date studies indicated the importance of DNA damage signaling in the regulation of PD-L1 expression following RT. DNA damage dependent PD-L1 expression is upregulated by ATM/ATR/Chk1 kinase activities and cGAS/STING-dependent pathway, proving the role of DNA damage signaling in PD-L1 induced expression. Checkpoint blockade immunotherapies (i.e., application of anti-PD-1 and anti-PD-L1 antibodies) combined with RT were shown to significantly improve the objective response rates in therapy of various primary and metastatic malignancies. Further improvements in the therapeutic potential of RT are based on combinations of RT with other immunotherapeutic approaches including vaccines, cytokines and cytokine inducers, and an adoptive immune cell transfer (DCs, NK cells, T cells). In the current review we provide immunological rationale for a combination of RT with various immunotherapies as well as analysis of the emerging preclinical evidences for these therapies.